Mutant mantis lunch ladies! - Hale, Bruce (Hale, Bruce. Monstertown mystery, 2017)
Best friends Benny and Carlos risk their lives to investigate when AJ reports seeing one of Monterrosa Elementary's beloved lunch ladies change into a giant mantis.